Implementation of Psychological and Social Assessment Services for Clients of the Integrated Narcotics Assessment Team at the National Narcotics Agency of East Java Province - Vania Sharira Hyacintha Prabaswari Mahadhini; Siti Jaro'ah (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This study aims to explore the implementation of psychological and social assessment services conducted by the Integrated Assessment Team at the National Narcotics Agency of East Java Province (BNNP Jawa Timur). Utilizing a descriptive qualitative method, the research involved intervi, observations, and documentation involving three drug abuse clients. The findings reveal that substance abuse is closely related to unresolved psychosocial stressors, including family pressure, economic hardship, peer influence, and emotional instability. Clients come from a variety of psychological and social backgrounds, including varying educational levels. Therefore, researchers sought to uncover how psychological and social factors contribute to clients' drug use tendencies. The role of the Integrated Assessment Team, composed of professionals from medical, legal, psychological, and social fields, is crucial in providing objective and comprehensive recommendations. The study underscores the significance of therapeutic communication, biopsychosocial assessments, and post-rehabilitation support to ensure long-term recovery and social reintegration for clients.